MotionHub: Middleware for unification of multiple body tracking systems - Ladwig, P.; Evers, K.; Jansen, E. J.; Fischer, B.; Nowottnik, D.; Geiger, C. (Proceedings of the 7th International Conference on Movement and Computing, 2020)
There is a substantial number of body tracking systems (BTS), which cover a wide variety of different technology, quality and price range for character animation, dancing or gaming. To the disadvantage of developers and artists, almost every BTS streams out different protocols and tracking data. Not only do they vary in terms of scale and offset, but also their skeletal data differs in rotational offsets between joints and in the overall number of bones. Due to this circumstance, BTSs are not effortlessly interchangeable. Usually, software that makes use of a BTS is rigidly bound to it, and a change to another system can be a complex procedure. In this paper, we present our middleware solution MotionHub, which can receive and process data of different BTS technologies. It converts the spatial as well as the skeletal tracking data into a standardized format in real time and streams it to a client (e.g. a game engine). That way, MotionHub ensures that a client always receives the same skeletal-data structure, irrespective of the used BTS. As a simple interface enabling the user to easily change, set up, calibrate, operate and benchmark different tracking systems, the software targets artists and technicians. MotionHub is open source, and other developers are welcome to contribute to this project.